Tax Disputes Stemming from the Use of Quantitative Techniques in Audits: Implications of Numerical Analysis, Correlation Testing, and Equalization Methods - Prayudi, Ikhsan Candra; Rosid, Arifin (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p20, 2025)
A significant proportion of evidentiary disputes in tax courts  stem from disagreements over tax assessments that rely on audit  techniques such as numerical analysis, correlation (linkage)  testing, and equalization. This study investigates the root causes  of tax disputes arising from the application of these techniques  and offers recommendations to reduce their incidence. To achieve  these objectives, the research adopts a qualitative approach,  utilizing content analysis of tax court rulings alongside thematic  analysis of interview data. Semi-structured interviews were  conducted with key stakeholders, including objection reviewers,  tax auditors, taxpayers or their consultants, and tax court judges.  The findings aim to inform policy and practice by providing  actionable recommendations that may help mitigate tax disputes  linked to the use of numerical analysis, correlation testing, and  equalization in tax audits.  Keywords: Tax disputes; evidence; examination techniques; analysis; and result discrepancies.